SAE Technical Paper Series 1996
DOI: 10.4271/960907
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Ground Transportation Systems (GTS) Project for Heavy Vehicle Drag Reduction

Abstract: A wind tunnel experimenta research program was conducted on a heavily instrumented Ground Transportation System (GTS) vehicle. The GTS baseline model represented a generic 1:8 scale Class-8 van-type tractor trailer geometry. Five base drag reduction add-on devices, instrumented with surface pressure ports, were also tested. These add-on devices included two ogive boattail shapes and three slant geometry devices.Six component force and moment data, surface pressure contours, and wake velocity surveys are presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 2 publications
5
38
0
Order By: Relevance
“…We present here an overview of the current experimental approach and several preliminary results provided for the integrated tractor-trailer benchmark geometry termed the Sandia Model [2]. The purpose of the tests are for validation of the computational fluid dynamics (CFD) models, and for further insight into truck flow phenomena.…”
Section: Methodsmentioning
confidence: 99%
“…We present here an overview of the current experimental approach and several preliminary results provided for the integrated tractor-trailer benchmark geometry termed the Sandia Model [2]. The purpose of the tests are for validation of the computational fluid dynamics (CFD) models, and for further insight into truck flow phenomena.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike the GTS model used in previous experimental (Croll et al 1996;Storms et al 2001) and computational (Salari et al 2004) studies, this model includes wheels; a schematic of the geometry is shown in Figure 2. For this study we have used GTS model dimensions corresponding to those of a 1/8-scale wind tunnel model.…”
Section: Simplified Heavy Vehicle (Gts): Geometrymentioning
confidence: 99%
“…We present herein an overview of the current experimental approach and results provided for the integrated tractor-trailer benchmark geometry termed the Ground Transportation System (GTS) [2]. Continuum Dynamics, Inc. has also provided boattail plates made to fit the GTS Model (Figure 1).…”
Section: Methodsmentioning
confidence: 99%